"The development of a through-plane reactive excitation technique for detection of pinholes in membrane-containing MEA sub-assemblies". (29th March 2019) - Ulsh, Michael; DeBari, Annalisa; Berliner, Jacob M.; Zenyuk, Iryna V.; Rupnowski, Peter; Matvichuk, Larissa; Weber, Adam Z.; Bender, Guido
Abstract: As markets for polymer-electrolyte-membrane fuel cells (PEMFC) expand, there continues to be a need for the development and implementation of in-line quality inspection techniques to enable high-volume manufacturing methods for membrane-electrode assemblies (MEAs). These techniques mitigate the potential impact of poor quality on the cost of MEA components by real-time identification of process-induced irregularities, which can result from the manufacturing process or subsequent handling of the material during assembly into a full MEA. A particular type of irregularity known to impact MEA lifetime is loss of membrane integrity, e.g. via a pinhole. In this work, we focus on development of a technique to detect pinholes in membrane-containing MEA sub-assemblies – as opposed to in just the membrane – using a reactive excitation strategy coupled with infrared thermography for detection. A specialized device is introduced and, using various MEA sub-assemblies, is shown to enable detection of pinholes in stationary samples. Multi-physics modeling is utilized to understand and predict the impact of various design and operational parameters of this technique. The feasibility of the technique is demonstrated through both modeling and in-situ results. For example, a detectable (≥1 °C) thermal response for a membrane pinhole of approximately 90 μm in diameter is measured in a fraction of a second. The observed detection time is considered to be appropriate for further exploration of the technique in an in-line configuration. Highlights: We have studied parametric effects for detection of membrane pinholes in MEAs. The technique is based on reactive gas excitation and infrared thermography. A specialized test stand was designed and constructed to enable the research. Multi-physics modeling was used to predict parametric effects. A 90-μm diameter pinhole was detected in less than 1 s.